Parallelism and Musical Structures in Ingrian and Karelian Oral Poetry - Kallio, Kati (Oral Tradition, 2019)
Listening to historical oral poetry usually means listening to sound recordings in the archives with no possibility to ask questions or compare performances by one singer in different performance arenas. Yet, when a greater amount of recordings from different singers and by different recorders is available, the comparison of these performances has the potential to reveal some locally shared understandings on the uses of poetic registers. In the present article, this setting is applied to examine the relationships of textual parallelism and musical structures in Kalevala-metric oral songs recorded from two Finnic language areas, Ingria and Karelia. Peer reviewed